2007
DOI: 10.1038/nrm2101
|View full text |Cite
|
Sign up to set email alerts
|

Soluble protein oligomers in neurodegeneration: lessons from the Alzheimer's amyloid β-peptide

Abstract: The distinct protein aggregates that are found in Alzheimer's, Parkinson's, Huntington's and prion diseases seem to cause these disorders. Small intermediates - soluble oligomers - in the aggregation process can confer synaptic dysfunction, whereas large, insoluble deposits might function as reservoirs of the bioactive oligomers. These emerging concepts are exemplified by Alzheimer's disease, in which amyloid beta-protein oligomers adversely affect synaptic structure and plasticity. Findings in other neurodege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

73
3,959
4
51

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 4,353 publications
(4,087 citation statements)
references
References 128 publications
73
3,959
4
51
Order By: Relevance
“…The imbalance in overall protein homeostasis is a crucial factor in the development of heritable age‐related neurodegenerative diseases and during normal aging (Dobson, 2003; Vacher et al ., 2005; Zhang et al ., 2005; Arslan et al ., 2006; Haass & Selkoe, 2007; Morimoto, 2008). Achieving and maintaining the correct three‐dimensional protein structure is a continuous struggle within cells.…”
Section: Introductionmentioning
confidence: 99%
“…The imbalance in overall protein homeostasis is a crucial factor in the development of heritable age‐related neurodegenerative diseases and during normal aging (Dobson, 2003; Vacher et al ., 2005; Zhang et al ., 2005; Arslan et al ., 2006; Haass & Selkoe, 2007; Morimoto, 2008). Achieving and maintaining the correct three‐dimensional protein structure is a continuous struggle within cells.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of soluble proteins into fibrillar amyloid deposits is a hallmark of a range of increasingly prevalent neurodegenerative disorders including Alzheimer's Disease (AD) and Parkinson Disease (PD) 1, 2, 3, 4. It has been reported that the species formed during the aggregation reactions have a toxic effect on cells 5, 6, 7, 8.…”
mentioning
confidence: 99%
“…It has been reported that the species formed during the aggregation reactions have a toxic effect on cells 5, 6, 7, 8. Several possible mechanisms of cellular damage have been identified with relative contributions that depend on both the concentrations and the types of aggregates present 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11. The aggregation process that results in the formation of oligomers may contribute to cellular damage 12, 13, 14, 15.…”
mentioning
confidence: 99%
See 2 more Smart Citations